Education, Science, and Technology - Zhuang, Dianzhou (Understanding Chinese culture, 2018)
Chapter 3, “Education, Science and Technology,” was written by the late Zhuang Dianzhou in the original work and translated by Ye Qingfen for this book. The chapter presents ancient China’s achievements in education, educational thought, and its representative educators; it also outlines the evolution of Chinese science and technology, with a focus on spectacular records in various scientific and technological fields after the establishment of the People’s Republic.